Pengaruh Jarak Tanam dan Pemangkasan terhadap Kualitas Silase Dua Varietas Jagung (Zea mays L.) - La Karimuna; Safitri Safitri; La Ode Sabaruddin (Jurnal Agripet, 2009)
Effects of crop arrangement and cutting on the silages quality of two varieties of maize (Zea mays L.)ABSTRACT. The objective of this experiment was to study the interaction effect of varieties, spacing and cutting on the quality of silage as foodstuff. The experiment had been conducted from January to April, 2007 at the experimental Garden of Faculty of Agriculture, University of Haluoleo. This experiment was arranged in Split-Split plot design with three factors. The first factor was variety as main plot, consisting of BISI-2 variety and local variety; the second factor was space arrangement as sub plot, consisting of 60 cm x 40 cm (J1), 75 cm x 40 cm (J2), 90 cm x 40 cm (J3), the third factor was cutting period as sub plot, consisting of no cutting (Po), cutting on 40 days (P1), and cutting on 55 days (P2). So that there were 2 x 3 x 3 x 3 = 54 experimental units. Analysis of variance was applied to know the effect of treatment. If so, least significant difference (LSD) 0.05 (95 %) confidence level was used. Variables observed was plant growth determining silages quality, consisting of quality of crude protein, crude fiber, crude fat, and water. Results of research revealed that interaction affect of spacing and cutting periods on 40 days of BISI-2 variety gave the best yield of plant growth for plant height. While the local variety tended to adverse effect of cutting. However, the quality of silages of two varieties tended to be similar. Every crop spacing had a positive effect of cutting on 40 days. The best quality of silages of two varieties was resulted from the interaction between spacing 75 cm x 40 cm and cutting of 40 days.